2013
DOI: 10.1038/ncomms3159
|View full text |Cite
|
Sign up to set email alerts
|

Strain and curvature induced evolution of electronic band structures in twisted graphene bilayer

Abstract: It is well established that strain and geometry could affect the band structure of graphene monolayer dramatically. Here we study the evolution of local electronic properties of a twisted graphene bilayer induced by a strain and a high curvature, which are found to strongly affect the local band structures of the twisted graphene bilayer. The energy difference of the two low-energy van Hove singularities decreases with increasing lattice deformation and the states condensed into well-defined pseudo-Landau leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
140
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 58 publications
12
140
0
Order By: Relevance
“…In particular, Landau level quantization was observed in a sequence of dI/dV spectra measured in a line across a graphene nanobubble on Pt(111), as shown in Figure 9(c), which arises from giant strain-induced pseudo-magnetic elds in excess of 300 Tesla in highly strained graphene nanobubbles formed on Pt(111) [107]. Similar phenomena were recently reported by Yan et al who observed the Landau level quantization of the strained graphene bilayer in a large pseudomagnetic eld of~100 Tesla [109].…”
Section: Weakly Interacting Graphene/metal Systemssupporting
confidence: 66%
“…In particular, Landau level quantization was observed in a sequence of dI/dV spectra measured in a line across a graphene nanobubble on Pt(111), as shown in Figure 9(c), which arises from giant strain-induced pseudo-magnetic elds in excess of 300 Tesla in highly strained graphene nanobubbles formed on Pt(111) [107]. Similar phenomena were recently reported by Yan et al who observed the Landau level quantization of the strained graphene bilayer in a large pseudomagnetic eld of~100 Tesla [109].…”
Section: Weakly Interacting Graphene/metal Systemssupporting
confidence: 66%
“…For example, effective gauge fields are introduced when lattice deformation of graphene takes place. Like the effective magnetic field, the produced effective gauge fields influence the Dirac fermions [180]. The Fermi level in undoped graphene lies at the Dirac point where the minimum conductivity values are achieved [181].…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…In Bernal stacking, the charge carriers of the graphene bilayer have a parabolic energy spectrum and exhibit chirality that resembles those associated with spin 1. However, a twist between the two layers splits the parabolic band touching into two Dirac cones [13][14][15][16][19][20][21][22][23][24] and changes the chirality of the low-energy quasiparticles to those of spin 1/2 [18,25]. This provides a facile route to tune the electronic properties of graphene bilayer.…”
Section: Introductionmentioning
confidence: 99%